Identifying gait events without a force plate during running: A comparison of methods - Leitch, J; Stebbins, J; Paolini, G; Zavatsky, AB (2011)
This paper presents a comparison of four different methods of identifying the times of foot-strike and toe-off during running based on gait marker trajectories. The event times predicted by the methods were compared to those identified using a force plate for both over-ground and treadmill running. The effect of using different threshold values for the detection of gait events using force plate data was also investigated, and as a result, all assessments of event detection accuracy were based on a cut-off value of 10. N. The most accurate method of foot-strike detection depended on whether the runner landed with a rear- or a mid-foot strike. For rear-foot-strike running, the best method of identifying foot-strike used the vertical acceleration profile of the posterior heel distal marker and the vertical position profile of the hallux marker. For mid-foot-strike running, the best method of identifying foot-strike used the vertical velocity profile of the mean positions of the posterior heel distal marker and a marker midway between the second and third metatarsal heads. The most accurate method of identifying toe-off did not depend on type of foot-strike and was based on the vertical acceleration and position profiles of the hallux marker. © 2010 Elsevier B.V.